The Curator’s Authority in The Management & Settlement of Bankruptcy Property - Novita, Tri Reni; Husna, M Faisal; Maryani, Halimatul (JURNAL AKTA, 2025)
One of the most thought processes of a company that's a lawful substance to borrow or utilize capital from third parties is the crave to extend the benefits that can be accomplished. The extra modern capital can be utilized to smooth the company's cash stream or commonly utilized as a company commerce improvement. A company is said to be bankrupt (bankrupt), when the company/individual is unable and unwilling to pay its debts. Therefore, in order to prevent creditors from collecting debtors and fighting over the assets of the bankrupt debtor, the law considers it necessary to regulate it, so that the debtors' debts can be paid in an orderly and fair manner. Bankruptcy law institutions emerged to regulate fair procedures regarding the payment of creditors' bills by being guided by the Civil Code (KUHPerdt), especially those contained in Articles 1131 and 1132 concerning privileged receivables, as well as using the Bankruptcy Law and the Suspension of Debt Payment Obligations (hereinafter referred to as the Bankruptcy and Suspension of Debt Payment Obligations). This article used combination of standardizing juridical strategies and experimental juridical strategies, which is carried out by centering on the ponder of the application of positive lawful rules or standards related to legitimate directions (laws). The purpose of this article is to examine the authority of the curator in managing and clearing bankruptcy assets related to the company's actors. The strategy utilized in composing this article is to utilize a combination strategy between standardizing juridical and experimental juridical strategies, which 1 is carried out by centering on the consider of the application of positive legitimate rules or standards related to lawful controls (laws), and after that related to the standards contained in liquidation, to be specific the guideline of adjust, the rule of commerce progression, the rule of equity, and the guideline of integration.